Díaz Cintas, J., & Nikoli?, K. (Eds.). (2018). Fast-forwarding with audiovisual translation. Bristol: Multilingual Matters - Gerber-Morón, Olivia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Book review